Analysis of The Influence of Service Quality, Price, and Reputation on Customer Loyalty with Customer Satisfaction as a Mediating Variable in a Freight Forwarding Company - Eli Sofah; Nelmida Nelmida; Sita Anisah Sholihah; Cecep Pahrudin; Edi Abdurachman (Dinasti Review, 2026)
This study examines the effects of service quality, price, and reputation on customer satisfaction and customer loyalty in the freight forwarding industry. The research is motivated by the need to identify key determinants of customer loyalty in an increasingly competitive logistics market. A descriptive quantitative approach was applied, with data collected from customers who have used freight forwarding services. The sample consisted of 250 respondents, determined using the Hair et al. formula (5 × number of indicators), and data were gathered through structured questionnaires. Structural Equation Modeling (SEM) was employed to analyze both direct and indirect relationships among variables. The results indicate that service quality, price, and reputation positively influence customer satisfaction, while customer satisfaction has a significant positive effect on customer loyalty. Furthermore, service quality and reputation indirectly affect loyalty through satisfaction, whereas the indirect effect of price through satisfaction is not statistically significant. These findings suggest that freight forwarding companies should focus on improving service quality and strengthening corporate reputation to enhance customer satisfaction and achieve sustainable customer loyalty.